OPTIMALISASI SISTEM ANTRIAN DI J&T EXPRESS BYPASS BUKITTINGGI DENGAN METODE SIMULASI - Rahma Dhani; Najwabilla Salshavira; Liza Efriyanti; Miftahur Rahmi; M. Raihan Alfandi (LPPM Unbaja, 2025)
This study aims to optimize the queuing system at the J&T Express Bukittinggi Bypass branch using a simulation method. The main problems identified are prolonged customer waiting times and long queues during peak hours, which negatively impact customer satisfaction and operational efficiency. To address these issues, this study employs a queue simulation method based on a mathematical model, enabling the analysis of queuing system performance and the evaluation of various improvement scenarios. Several scenarios were tested, including adding service counters, reducing service times, and rearranging the counter layout. Data collected through direct observation were analyzed to determine customer arrival times, service times, and queue lengths. The simulation results indicate that adding service counters significantly reduces customer waiting times, while reducing service times accelerates processes and shortens queues. Additionally, rearranging the counter layout has proven effective in balancing customer distribution. In conclusion, the application of queue simulation as a tool for analyzing and optimizing queuing systems can enhance operational efficiency, reduce waiting times, and improve the customer experience. This study provides a valuable contribution to the management of queuing systems in the logistics sector, particularly at J&T Express.